Analisis Perbandingan Return On Asset, Return On Equity, Debt to Equity Ratio, dan Earning Per Share Sebelum dan pada Saat Pandemi Covid-19 - Almas Zannah; Azib (Bandung Conference Series: Business and Management, 2022)
Abstract. This study aims to determine the significance of the transportation shares listed on the Indonesia Stock Exchange before and during the covid-19 pandemic. This study used a descriptive method using secondary data analysis in the form of the company’s quarterly financial statement. The research observation period was quarter 3 of 2019 and quarter 3 of 2020. The sampling technique used purposive sampling and obtained a research sample of 15 companies in the transportation sector listed on the IDX. The analytical tool used is the parametric paired sample t-test for return on equity, debt to equity ratio, earning per share, while the return on asset test used the Wilcoxon singed rank test with the help of SPSS program 25. The results of the study show that there are significant differences in return on assets, return on equity, and earnings per share before and during covid-19 in transportation sector companies, while the debt to equity ratio variable has no significant differences before and during covid-19 in companies. transportation sector. Abstrak. Penelitian ini bertujuan untuk mengetahui seberapa signifikan perbandingan return on asset, return on equity, debt to equity ratio, dan earning per share perusahaan sektor transportasi yang terdaftar di Bursa Efek Indonesia sebelum dan saat pandemi covid-19. Penelitian ini menggunakan metode deskriptif dengan menggunakan analisis data sekunder berupa laporan keuangan berupa periode triwulan perusahaan tersebut. Periode pengamatan penelitian adalah kuartal 3 tahun 2019 dan kuartal 3 tahun 2020. Teknik pengambilan sampel menggunakan purposive sampling dan diperoleh sampel penelitian sebanyak 15 perusahaan sektor transportasi yang terdaftar di BEI. Alat analisis yang digunakan adalah uji parametric paired sample t-test untuk return on equity, debt to equity ratio, dan earning per share. Sedangkan pengujian return on asset digunakan uji Wilcoxon singed rank test dengan bantuan program SPSS 25. Hasil penelitian menunjukan adanya perbedaan yang signifikan return on asset, return on equity, dan earning per share sebelum dan saat adanya covid-19 pada perusahaan sektor transportasi, sedangkan variabel debt to equity ratio tidak terdapat perbedaan yang signifikan sebelum dan saat covid-19 pada perusahaan sektor transportasi.